Etika Penggunaan Kecerdasan Buatan Dalam Perspektif Islam: Mitigasi Risiko Dan Optimalisasi Manfaat - Fatimah Yanti Sinaga (Sekolah Tinggi Ilmu Tarbiyah Al-Bukhary Labuhanbatu, 2025)
The development of artificial intelligence (AI) technology has a significant impact on various aspects of life, including among Muslims. This article discusses the ethics of AI usage from an Islamic perspective, emphasizing relevant Sharia principles. Through a literature review approach, this article examines how AI can be optimally utilized in accordance with the objectives of Sharia (maqasid sharia), namely the preservation of religion, life, intellect, lineage, and property. It was found that Islam supports technological innovation as long as it does not contradict moral values, such as justice, responsibility, transparency, and respect for individual rights. AI technology is viewed as a tool that can bring benefits, but it must still be used ethically and responsibly to avoid potential harm (mafsadah). Islamic ethical guidelines such as maslahah, amanah, ‘adl, and tawazun serve as important frameworks in determining the appropriateness and acceptability of using AI in daily life. Thus, the utilization of AI in accordance with Islamic values can contribute positively to the welfare of the community and the advancement of civilization.